Clinostomum complanatum (Digenea, Clinostomidae) density in Rhamdia quelen (Siluriformes, Pimelodidae) from South Brazil - Vianna,Rogério Tubino (2005)
The density of Clinostomum complanatum metacercariae by the body regions and among the size classes of Rhamdia quelen was compared. The host size classes were defined by cluster analysis, using weight and total length as attributes. These values were related with environmental characteristics and host biological data. In all the host size classes H and PeF, CF and PF, and P and AF regions pairs, showed similar density (tested by X² test). The hosts with 30-36 cm showed largest parasite density in all the regions, except in CAV. Fishes smaller than 11 cm did not show significant differences of parasite density in all body regions. In the other classes, H was the most infected region, followed by PeF. The results suggested that the environmental conditions had little importance on the host colonization by metacercariae.